ACCOUNTABILITY PRESSURE AS DEBIASER FOR CONFIRMATION BIAS IN INFORMATION SEARCH AND TAX CONSULTANT’S RECOMMENDATIONS - Fauzan - Misra; Slamet Sugiri; Eko Suwardi; Ertambang Nahartyo (Journal of Indonesian Economy and Business (JIEB), 2019)
Introduction: This study examines the influence of accountability pressure toward information search behavior and the subsequent tax recommendation.  Background Problem: Prior research has shown that tax consultants are subject to confirmation bias during their information search when providing recommendations to their clients. Nevertheless, less attention has been given to identifying boundary condition or mitigating factors. This study proposes accountability pressure to mitigate such bias. Novelty: This study broadens the understanding of the effect of different accountability pressures on an individual’s effort and judgement making. Research Method: The research was conducted by an experimental approach using a 1x2 between-subjects design using an Internet-based instrument. Accountability pressure is manipulated into 2 levels (strong or weak). The experiment involved 82 tax professionals. Findings: The results show that accountability pressures influence the depth of the consultant information search. That is, a tax consultant those faced a high accountability pressure performed a deep search, while those who faced a weak accountability pressure conducted a shallow search. Then, a deep search leads to more conservative recommendations, while a shallow search leads to an aggressive recommendation. Furthermore, the results of interaction and simple effect tests show that the information search depth can mitigate confirmation bias occurred during information search processes. Conclusion: These findings imply that accountability within the organization needs to get more attention from tax consultants. While any prior research found that confirmation bias was proofed to have pervasive character and hard to be eliminated,  this study pointed out that the accountability pressure could mitigate such bias.